Interrelation Of The Pedagogical Culture And Education Of Youth In The Analysis Of The Dynamics Of Age Differences In The Legal Modern Society: Kazakhstan, As A Model Of The Modern Legal State - Lepeshev, D.; Kalaganov, B.; Ilimkhanova, L.; Seriyev, B; Nurtazina, R; Kopbaeva, L.; Sabyr, A (Opción, 2019)
The interrelation of pedagogical culture and education of youth in the analysis of the dynamics of age differences in the multiethnic society of Kazakhstan is of interest because of its multifacetedness and undoubted relevance and vital- ity. This is due to the very nature of the society of Kazakhstan: poly-ethnic, multicultural and poly-confessional. Historically, there are people of different nationalities living in the country, professing different denominations with dif- ferent cultural values and rules. Pedagogical science should take into account all these moments and offer educational methods that are universal and com- prehensive and meet the interests of all groups of young people, regardless of their religion or nationality. Pedagogical science investigates problems and questions related to obtain- ing preschool, secondary and vocational education. In Kazakhstan, uni- versities that train specialists in this field are widely represented: they are not only national and state, but also private higher educational institutions. The subject of the study was the interrelation between pedagogical cul- ture and the education of young people in the analysis of the dynamics of age differences. It is difficult to challenge the inseparable connection of these concepts, as the level of education and literacy of the population, not to mention adherence to the norms of morality, spirituality and ethics, is directly related to the development of pedagogy and the quality of train- ing of specialized specialists. Last decades all branches of vital activity of Kazakhstan underwent serious changes and perturbations, education did not remain untouched. It is in the field of education and pedagogy that the age differences, which caused the difference in the worldview, mentality and life values of older people raised in certain ideals and needs, and the younger generation who grew up in completely different economic, polit- ical and social conditions, were very clearly manifested.